Pengaruh Non Performing Loan (NPL) dan Capital Adequacy Ratio (CAR) terhadap Profitabilitas (ROA) Perusahaan Perbankan Tahun 2014 - 2023 - Herlyana Dewi Cahyani; Amirudin Amirudin (Jurnal Publikasi Ilmu Manajemen, 2024)
This study aims to empirically assess the impact of Non-Performing Loans (NPL) and Capital Adequacy Ratio (CAR) on Profitability (ROA) for banking companies listed on the Indonesia Stock Exchange from 2014 to 2023. The research employs purposive sampling, resulting in a sample of 7 companies with 10 years of data. The study uses a quantitative approach with secondary data, analyzing panel data through E-views software version 12.0. Methods include multiple linear regression, classical assumption tests, panel data regression analysis, coefficient of determination, T-tests, and F-tests. The findings indicate that, individually, Non-Performing Loans (NPL) have a significant negative effect on Return On Assets (ROA), while Capital Adequacy Ratio (CAR) significantly impacts Return On Assets (ROA). Additionally, both Non-Performing Loans (NPL) and Capital Adequacy Ratio (CAR) have a significant combined effect on Return On Assets (ROA).